Geographic distribution and environmental risk factors of lymphoma in dogs under primary‐care in the UK. (10th November 2019) - Schofield, I.; Stevens, K. B.; Pittaway, C.; O'Neill, D. G.; Fecht, D.; Dobson, J. M.; Brodbelt, D. C.
Abstract : Objectives: To integrate external data sources with VetCompass postcode data to explore the spatial distribution and examine potential associations with environmental risk factors in dogs diagnosed with lymphoma at primary care veterinary practices. Materials and Methods: Cases of lymphoma were identified from electronic patient records of 455, 553 dogs under primary veterinary care during 2013 in the UK. Cases were defined as either laboratory‐confirmed or non‐laboratory‐confirmed. Disease maps at the postcode‐district level were used to define the geographic distribution of lymphoma incidence and spatial clustering was explored. Environmental risk factors from external data sources were transferred to a compatible format and logistic regression modelling was used to examine associations between environmental herbicide, fungicide and radon concentrations with lymphoma. Results: From the denominator population of 455, 553 dogs, 279 lymphoma cases (187 with laboratory confirmation and 93 without) were identified. Heterogeneous geographic variation was observed with weak evidence of clustering around London and the south‐west of England. Herbicide and fungicide exposures were weakly associated with a diagnosis of lymphoma in the univariable analysis. After accounting for the age at diagnosis and breed in the multivariable analysis, herbicide exposure was associated with a diagnosis of lymphoma. Clinical Significance: The heterogeneous distribution of lymphoma in UK dogs provides further evidence for geographic variation of lymphoma, perhaps in part associated with underlying environmental risk factors. The results suggest an association between environmental herbicide and canine lymphoma.